An approach towards the knowledge of Iberian high mountain calcareous grasslands - Gavilán, Rosario G.; Díez-Monsalve, Estrella; Izquierdo, José Luis; Gutiérrez-Girón, Alba; Fernández-González, Federico; Sánchez-Mata, Daniel (Lazaroa, 2012)
We have carried out a study on the pastures growing at high altitudes on calcareous substrata in the central-eastern Iberian Peninsula. The study comprised two areas: the Gúdar and Javalambre mountain areas, and the calcareous outcrops of the Sierra de Guadarrama. Two datasets were analysed: relevés taken in the Sierra de Guadarrama in the summer of 2010; and the relevés of Rivas Goday & Borja (1961) above 1700 m of altitude. The results highlighted the similarities and differences between both datasets, and we have recognized the new association Festuco curvifoliae-Astragaletum mutici for the Sierra de Guadarrama high-mountain calcareous grasslands, with a presence on both types of substrata.